2020
DOI: 10.1083/jcb.201911120
|View full text |Cite
|
Sign up to set email alerts
|

Collective invasion induced by an autocrine purinergic loop through connexin-43 hemichannels

Abstract: Progression of epithelial cancers predominantly proceeds by collective invasion of cell groups with coordinated cell–cell junctions and multicellular cytoskeletal activity. Collectively invading breast cancer cells express the gap junction protein connexin-43 (Cx43), yet whether Cx43 regulates collective invasion remains unclear. We here show that Cx43 mediates gap-junctional coupling between collectively invading breast cancer cells and, via hemichannels, adenosine nucleotide/nucleoside release into the extra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 94 publications
0
13
0
Order By: Relevance
“…We observed that NB cells displayed a spectrum of distinct behaviours within the organoid populations; representative images of each are shown in Figure 1 B. To classify the observed phenotypes, we used previously published terminology that is based on the visual appearance of organoids and the presence and cellular distribution of actin filaments [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. NB organoids commonly invaded as collective strands where adhesion between neighbouring cells was maintained.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that NB cells displayed a spectrum of distinct behaviours within the organoid populations; representative images of each are shown in Figure 1 B. To classify the observed phenotypes, we used previously published terminology that is based on the visual appearance of organoids and the presence and cellular distribution of actin filaments [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. NB organoids commonly invaded as collective strands where adhesion between neighbouring cells was maintained.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have described similar modes of multicellular migration where leading cells proteolytically degrade the ECM, creating a track that is widened by following cells [ 18 ]. Collective strands have been reported for breast cancer cells in 3D in vitro and in vivo models [ 17 , 19 ], for melanoma cells using intravital imaging [ 20 ] and clusters of circulating tumour cells have been identified in patients with metastatic disease [ 33 ]. In a small study of 28 NB patients, one circulating tumour cell cluster was identified in a high-risk patient with distant lymph node metastasis [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the conserved cytokeratin 14 (K14 + ) basal epithelial program orchestrates collective leader-follower cell behaviors during tumor cell invasion in 3D Type 1 Collagen ( 19 ). Friedl and colleagues demonstrated that leader cell function depends on a gap junction Cx43-dependent/ADORA1 axis in mediating collective cancer cell invasion ( 20 ). Interestingly, cadherins and ECM confinement further cooperate to determine unjamming transitions, coordinated vs. uncoordinated collective cell movements, and fluidization of tumor cells, impacting states of cell transit at matrix bottlenecks ( 21 ).…”
Section: Models Of Metastasismentioning
confidence: 99%
“…Subsequent studies have also shown pro-metastatic roles for hemichannels on cancer cells. Recent work showed that breast cancer cell collective invasion occurred via hemichannel-released adenosine nucleosides/nucleotides, which activated purinergic receptors in an autocrine fashion to promote leader cell function [ 187 ]. Finally, a fascinating report suggested that, in addition to the passage of small molecules, hemichannels can also function for adhesion.…”
Section: Mechanistic Roles Of Connexins In the Major Cancer Phenotmentioning
confidence: 99%